Analysis of the Impact of Change Management Implementation on an Organization - Diana Diana; Nuri Aslami (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Change is something that cannot be avoided, especially in an organizational environment, changes will often occur. Transformation or change in an organization has become a global issue since the discovery of the industrial revolution, therefore an organizational leader must be able to carry out various organizational changes and innovations and cannot escape the inevitable changes because this is what makes a leader carry out various organizational changes and innovations and cannot escape the inevitable changes because this is what makes a leader be a winner in business competition. Companies must be able to keep up with changes by carrying out organizational development. Therefore, the author conducted research to find out what are the impacts of implementing change management, things that affect change management and obstacles in change management. This study uses a qualitative method with a literature approach from several sources. The results of this study indicate that the impact of the implementation of change management on the organization affects the success of the company in the future.